High frequencies of adaptive NK cells are associated with absence of coronary plaque in cytomegalovirus infected people living with HIV. Issue 38 (23rd September 2022) - Alsulami, Khlood; Sadouni, Manel; Tremblay-Sher, Daniel; Baril, Jean-Guy; Trottier, Benoit; Dupuy, Franck P.; Chartrand-Lefebvre, Carl; Tremblay, Cécile; Durand, Madeleine; Bernard, Nicole F.
Abstract : The objective of this study was to evaluate whether adaptive NKG2C + CD57 + natural killer (adapNK) cell frequencies are associated with pre-clinical coronary atherosclerosis in participants of the Canadian HIV and Aging Cohort Study. This cross-sectional study included 194 Canadian HIV and Aging Cohort Study participants aged ≥ 40 years of which 128 were cytomegalovirus (CMV) + people living with HIV (PLWH), 8 were CMV − PLWH, 37 were CMV mono-infected individuals, and 21 were neither human immunodeficiency virus nor CMV infected. Participants were evaluated for the frequency of their adapNK cells and total plaque volume (TPV). TPV was assessed using cardiac computed tomography. Participants were classified as free of, or having, coronary atherosclerosis if their TPV was "0" and ">0, " respectively. The frequency of adapNK cells was categorized as low, intermediate or high if they constituted <4.6%, between ≥4.6% and 20% and >20%, respectively, of the total frequency of CD3 − CD56 dim NK cells. The association between adapNK cell frequency and TPV was assessed using an adjusted Poisson regression analysis. A greater proportion of CMV + PLWH with TPV = 0 had high adapNK cell frequencies than those with TPV > 0 (61.90% vs 39.53%, P = .03) with a similar non-significant trend for CMV mono-infected participants (46.15% vs 34.78%). The frequency of adapNK cells was negatively correlated with TPV. A high frequency of adapNK cells was associated with a relative risk of 0.75 (95% confidence intervals 0.58, 0.97, P = .03) for presence of coronary atherosclerosis. This observation suggests that adapNK cells play a protective role in the development of coronary atherosclerotic plaques.